Age and Paleoenvironmental Significance of the Frazer Beach Member—A New Lithostratigraphic Unit Overlying the End-Permian Extinction Horizon in the Sydney Basin, Australia - McLoughlin, Stephen; Nicoll, Robert S.; Crowley, James L.; Vajda, Vivi; Mays, Chris; Fielding, Christopher R.; Frank, Tracy D.; Wheeler, Alexander; Bocking, Malcolm (Frontiers in Earth Science, 2021)
The newly defined Frazer Beach Member of the Moon Island Beach Formation is identified widely across the Sydney Basin in both outcrop and exploration wells. This thin unit was deposited immediately after extinction of the Glossopteris flora (defining the terrestrial end-Permian extinction event). The unit rests conformably on the uppermost Permian coal seam in most places. A distinctive granule-microbreccia bed is locally represented at the base of the member. The unit otherwise consists of dark gray to black siltstone, shale, mudstone and, locally, thin lenses of fine-grained sandstone and tuff. The member represents the topmost unit of the Newcastle Coal Measures and is overlain gradationally by the Dooralong Shale or with a scoured (disconformable) contact by coarse-grained sandstones to conglomerates of the Coal Cliff Sandstone, Munmorah Conglomerate and laterally equivalent units. The member is characterized by a palynological ‘dead zone’ represented by a high proportion of degraded wood fragments, charcoal, amorphous organic matter and fungal spores. Abundant freshwater algal remains and the initial stages of a terrestrial vascular plant recovery flora are represented by low-diversity spore-pollen suites in the upper part of the unit in some areas. These assemblages are referable to the Playfordiaspora crenulata Palynozone interpreted as latest Permian in age on the basis of high precision (CA-IDTIMS) dating of thin volcanic ash beds within and stratigraphically bracketing the unit. Plant macrofossils recovered from the upper Frazer Beach Member and immediately succeeding strata are dominated by Lepidopteris (Peltaspermaceae) and Voltziopsis (Voltziales) with subsidiary pleuromeian lycopsids, sphenophytes, and ferns. Sparse vertebrate and invertebrate ichnofossils are also represented in the Frazer Beach Member or in beds immediately overlying this unit. The Frazer Beach Member is correlative, in part, with a thin interval of organic-rich mudrocks, commonly known as the ‘marker mudstone’ capping the Permian succession further to the north in the Bowen, Galilee and Cooper basins. The broad geographic distribution of this generally <5-m-thick mudrock unit highlights the development in eastern Gondwana of extensive, short-lived, shallow lacustrine systems with impoverished biotas in alluvial plain settings in the immediate aftermath of the end-Permian biotic crisis.